Copper-mediated arylation with arylboronic acids: Facile and modular synthesis of triarylmethanes - Rao, H. Surya Prakash; Rao, A. Veera Bhadra (Beilstein Journal of Organic Chemistry, 2016)
A facile and modular synthesis of triarylmethanes was achieved in good yield via a two-step sequence in which the final step is the copper(II)-catalyzed arylation of diarylmethanols with arylboronic acids. By using this protocol a variety of symmetrical and unsymmetrical triarylmethanes were synthesized. As an application of the newly developed methodology, we demonstrate a high-yielding synthesis of the triarylmethane intermediate towards an anti-breast-cancer drug candidate.
Keywords: copper; modular synthesis; triarylmethanes